A mathematical formulation for calculating temperature dependent friction coefficient values: Application in friction stir welding (FSW) - Meyghani, B. (Trans Tech Publications Ltd, 2017)
High rotational motion from the welding tool generates a significant amount of the heat during friction stir welding (FSW). Basically, during FSW the heat is mostly coming from the frictional force between the tool shoulder and the plates. Therefore, a precise calculation of the friction coefficient can increase the accuracy of the finite element analysis (FEA) of the process. However, researchers have applied constant values, and that causes a gap between the reality and the simulated model especially after the welding plunging step. In this study, a mathematical formulation is proposed in order to calculate the temperature dependent values of the friction coefficient and also to explore the influence of the temperature in the friction coefficient. To solve the governing equations of the process, the MATLAB® software is used. The results indicate that, from 25°C to the AA 6061-T6 melting point (580°C), the values of the friction coefficient fall steadily in a range of 0.207089 to 0.000582. Furthermore, the material shear stress and the material yield stress decrease consistently as the temperature rises. Consequently, the influence of the temperature in the contact input parameters and the material properties are discussed in detail and a good correlation with the published results is achieved. © 2017 Trans Tech Publications, Switzerland.